2022
DOI: 10.1038/s41586-022-04908-6
|View full text |Cite
|
Sign up to set email alerts
|

A male steroid controls female sexual behaviour in the malaria mosquito

Abstract: Insects, unlike vertebrates, are widely believed to lack male-biased sex steroid hormones1. In the malaria mosquito Anopheles gambiae, the ecdysteroid 20-hydroxyecdysone (20E) appears to have evolved to both control egg development when synthesized by females2 and to induce mating refractoriness when sexually transferred by males3. Because egg development and mating are essential reproductive traits, understanding how Anopheles females integrate these hormonal signals can spur the design of new malaria control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The UAS- CG5644 line was further crossed to the phm-GAL4 driver at 25 °C, resulting in 66 misexpression adults surviving compared to 115 balancer adults (proportion = 0.365, 95% CI: 0.295– 0.439, p = 0.0003, binomial test), suggesting PG misexpression of CG5644 can also disrupt development. These data are consistent with the hypothesis that CG5644 encodes an ecdysteroid 22-kinase, previously proposed based on 1:1 orthology to AgEcK2 in Anopheles gambiae (Peng et al 2022; Scanlan & Robin 2023). The lack of developmental arrest seen in tub>CG31300 and tub>JhI-26 individuals is consistent with previously published experimental data (Liu et al 2014; Scanlan et al 2022).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The UAS- CG5644 line was further crossed to the phm-GAL4 driver at 25 °C, resulting in 66 misexpression adults surviving compared to 115 balancer adults (proportion = 0.365, 95% CI: 0.295– 0.439, p = 0.0003, binomial test), suggesting PG misexpression of CG5644 can also disrupt development. These data are consistent with the hypothesis that CG5644 encodes an ecdysteroid 22-kinase, previously proposed based on 1:1 orthology to AgEcK2 in Anopheles gambiae (Peng et al 2022; Scanlan & Robin 2023). The lack of developmental arrest seen in tub>CG31300 and tub>JhI-26 individuals is consistent with previously published experimental data (Liu et al 2014; Scanlan et al 2022).…”
Section: Resultssupporting
confidence: 92%
“…Plausible, alternative ecdysteroid substrates for Wall are 3-dehydroecdysteroids and 3-epiecdysteroids, which are produced in the fat body and epidermis of larvae (Sommé-Martin et al 1988a, 1988b and may have signalling functions in D. melanogaster (Sommé-Martin et al 1990;Baker et al 2003). The physiological functions of these modified ecdysteroids are still unclear in D. melanogaster, but intriguingly, 3-dehydro-20E was recently found to modulate female reproductive physiology in the mosquito Anopheles gambiae (Peng et al 2022). Additionally, Cavigliasso et al (2023) recently suggested fezzik (fiz) encodes an ecdysteroid oxidase that adaptively modulates larval growth rate under malnutrition in D. melanogaster (Grenier et al 2023;Glaser-Schmitt & Parsch 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During mating, males transfer seminal fluid proteins that trigger the switch between virgin and mated female states. The transition involves a series of molecular, morphological, behavioral and physiological changes, and occurs in rapid and sustained phases [27][28][29][30][31]. Short-term post-mating responses occur during the first 24 h, while long-term post-mating responses can last up to two weeks after mating [27][28][29][30]32].…”
Section: Introductionmentioning
confidence: 99%